(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Corrective exercises, by which we mean correcting the wrong movements that a player has arisen during the performance of the sporting skill and incorrect positions that affect directly or indirectly the performance. The corrective exercises are of great importance that lies in improving skills and gaining the connection of the movement parts and that the most important benefit of corrective exercises is the expansion of sensory perception at the player, especially if those corrective exercises are prepared according to the biomechanical variables that contribute to the success of the performance significantly, as organizing the corrective exercises and the use of scientific methods and investing educational methods based on the correct foundations are the scientific approach that is intended to raise the educational level and achieve the goals of the educational process effectively and make these exercises tailored to the player’s desires and inclinations; to achieve additional learning experiences. The importance of the research was manifested in the study of one of the most important basic skills in the game of football, namely, the scoring skill, which is one of the main pillars on which all sports teams depend to settle the matches. As a result, the researchers decided to put corrective exercises to correct the errors that occur during the performance that lead to Teaching and developing some biomechanical variables to perform scoring skill from consistency and in order to achieve positive aspects of learning and overcome negative aspects to achieve accuracy in scoring. As for the research problem, it was manifested in the lack of studies and research that delve into the skill of accurate soccer scoring from a mechanical point of view, and if available, they have overlooked the aspect of determining the biomechanical values for scoring a man as well as not touching on corrective exercises to evaluate performance in the scoring skill of persistence. To scoring the man as well as not to address the corrective exercises to evaluate the performance in the scoring skill from persistence.